The Instrumental Framework to Measuring Environmental Awareness - Kencanasari, R. A. Vesitara; Surahman, Usep; Permana, Asep Yudi (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2019)
Environmental awareness needs to be increased because it plays an important role for the survival of life. To find out the level of public awareness of the environment it is necessary to conduct a workshop or environmental awareness training. The purpose of this study is to identify and generate an instrument indicator to measure the environmental awareness. This article looks at a variety of relevant literature in order to explore the aspects that must be present In the instrument to measuring the environmental awareness level. The literature study results are obtained the aspects that must have to consist of two aspects namely pro-environment and not pro-environment, in which indicators are made from the start of knowledge, attitudes and behavior. The implication of this literature review is to provide information and recommend a set of a framework to academics in making instruments measuring the level of public awareness of the environment.